Development of multiparametric kinetic data and analytics workflows for the generation of an hiPSC-cardiomyocyte based cardiovascular model - Raniga, Kavita (2024)
It is widely acknowledged that many lifesaving drugs (e.g. cancer treatments) adversely affect the heart, potentially leading to irreversible myocardial injury and dysfunction. Drug-induced cardiotoxicity is characterized by functional and/or structural damage to the cardiovascular system and is a major reason for attrition during drug development. In the pharmaceutical industry, early-stage in vitro assessment of cardiovascular liabilities primarily centers around the assessment of cardiac function, using single-cell type-model systems. Over recent years, human pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have become an attractive platform for capturing the effects of putative drugs. The functional assessment of hiPSC-CMs for toxicity screening presents several limitations. Firstly, they lack the physiological responses to enable integrated risk assessment, such as phenotypic immaturity and the absence of cardiac vascular and/or stromal cells. Secondly, they require cellular manipulation, which interferes with cell function. For example, the use of a fluorescence calcium-sensitive dye can be cytotoxic with prolonged exposure. Lastly, they offer limited mechanistic insights for compound classes. These considerations are included in paper I (Raniga et al., Cell Stem Cell, 2023).